A new species and new continental record for the genus Aclitus Foerster (Hymenoptera: Braconidae, Aphidiinae) - Martens, Abigail P.; Haimowitz, Larry; Shaw, Scott R.; Johnson, Paul J. (Zootaxa, 2026)
Aclitus wyomingensis Martens new species is described and Aclitus Foerster is reported from North America for the first time. A revised key to all described Aclitus species is presented, and the potential host associations and biology of Aclitus species are summarized.